Modern Methods for Treating Severe Acne (Eurasian Medical Research Periodical, 2024)
Acne is one of the most well-known chronic recurrent skin diseases, affecting mostly young people. The disease makes a significant negative contribution to the patient’s psycho-emotional sphere and social adaptation, often accompanied by the development of dysmorphophobia and other mental disorders. Despite the apparent simplicity and clarity of the diagnosis. Acne treatment is aimed at preventing pathogenetic factors. Topical therapy plays a major role in the treatment of mild to moderate acne. A single series of studies has demonstrated the great effectiveness of topical retinoids in their anti-comedogenic and anti-comedogenic properties.Anti-inflammatory effect, as well as topical antibacterial agents. Treatment with these drugs is carried out strictly according to indications and under the supervision of a dermatologist with regular conduct of certain laboratory tests. Currently, a method for treating acne has been developed, taking into account the clinical form and degree severity, which helps to increase the effectiveness of therapy, as well as accordingly, the patient’s quality of life [1]. Topical agents are the first line of treatment for mild to moderate acne and can be used as part of complex therapy together with systemic antibiotics or retinoids for more severe forms of acne that do not respond to topical therapy